The ties that bind: negotiating relationships in early Jewish and Christian texts, contexts, and reception history : essays in honor of Adele Reinhartz - Kobel, Esther; Brant, Jo-Ann A.; Warren, Meredith J. C.; Bowden, Andrew M.; Reinhartz, Adele (Library of New Testament studies, 2023)
Friendship and other intimate (but not always amicable) relationships have received some attention in the greater field of research on early Judaism and Christianity, though not as much as deserved. This volume celebrates and builds upon the life-long work of Adele Reinhartz, covering the various permutations of relationships that can be found in the Gospel of John, the wider corpus of early Jewish and Christian literature, and cinematic re-imaginings thereof. While the issue of whether one can 'befriend' the Fourth Gospel in light of the book's legacy of antisemitism is central to many of the essays in this volume, others address other more or less likely friendships: Pilate, Paul, Lazarus, Judas, or Mary Magdalene. Likewise, the bonds between ancient texts and contemporary retellings of their stories feature prominently, with contributors asking what kinds of relationships filmmakers encourage their audiences to have with their subjects. This volume explores some of the rich variety of relationships in the ancient world, and unpacks the intricate and dynamic processes and interactions by which human relationships and societies are generated, maintained, and dissolved